The Effect of Financial Literacy, Economic Literacy, and Entrepreneurial Literacy on Entrepreneurial Behavior - Susanti Susanti; Reza Ayu Palupi; Ernanda Nur Hamidah (Dinamika Pendidikan, 2022)
This study aimed to determine the effect of economic literacy, financial literacy, and entrepreneurial literacy on entrepreneurial behavior for State High School Students in Surabaya. This study used quantitative research with population of class XI and XII students from several of all public schools in Surabaya. Sampling used purposive samples with 50 respondents. Data collection techniques used questionnaires and tests and used descriptive analysis techniques and multiple linear regression analysis with classical assumption test, namely normality test, multicollinearity test, heteroscedasticity test by using SPSS. The results of this study are (1) economic literacy, financial literacy, and entrepreneurial literacy had a simultaneous effect on entrepreneurial behavior with F-count of 29.925 F-table 2.73 and a significance of 0.000 0.05. (2) Economic literacy partially had a significant effect on the entrepreneurial behavior of public high school students in Surabaya. (3) Financial literacy did not partially affect the entrepreneurial behavior of State Senior High School students in Surabaya. (4) entrepreneurial literacy partially had a significant effect on the entrepreneurial behavior of state high school students in Surabaya. Based on the conclusions above, researchers provide suggestions in the form of support so that in the future students are able to manage finances wisely, students continue to deepen their knowledge of finance, economics and entrepreneurship from various sources so that they can improve entrepreneurial behavior and further researchers are expected to be able to develop similar research by adding other independent variables and adding moderating variables with the hope can provide more accurate results regarding entrepreneurial behavior.